2016
DOI: 10.3349/ymj.2016.57.6.1531
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Laparoscopic Adenomyomectomy for Patients Who Want to Preserve Fertility

Abstract: An adenomyomectomy is a conservative-surgical option for preserving fertility. Conventional laparoscopic adenomyomectomies present difficulties in adenomyoma removal and suturing of the remaining myometrium. Robot-assisted laparoscopic surgery could overcome the limitations of conventional laparoscopic surgery. Four patients with severe secondary dysmenorrhea and pelvic pain visited Seoul St. Mary's Hospital and were diagnosed with adenomyosis by pelvic ultrasonography and pelvic magnetic resonance imaging (MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 7 publications
1
9
2
Order By: Relevance
“…Chung et al [20] have reported the feasibility of robot-assisted laparoscopic adenomyomectomy. The mean operative time was 159.25 minutes, and the EBL was 117.5 mL.…”
Section: Discussionmentioning
confidence: 99%
“…Chung et al [20] have reported the feasibility of robot-assisted laparoscopic adenomyomectomy. The mean operative time was 159.25 minutes, and the EBL was 117.5 mL.…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive laparoscopic surgery is the mainstream of modern surgery; however the surgeon could not access lesions in the uterus and deep lesions are easily missed [ 12 , 17 , 18 ]. In addition, the extent of resection is definitely less than that of laparotomy and suture and haemostasis is also quite difficult, resulting in a relatively high postoperative recurrence rate [ 19 ]. Therefore, we do not recommend a laparoscopic approach for this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of robotic surgery is that it has better visual field, with 3D high definition and the robotic arm has an endowrist with better range of movement in comparison to standard laparoscopy, allowing better suturing similar to laparotomic suturing. Therefore, this method has been suggested to be preferential to standard laparoscopy, however there is limited data on its use and bigger trials are required to identify benefits of robotic surgery over laparoscopy [11].…”
Section: Robot-assisted Laparoscopic Adenomyomectomymentioning
confidence: 99%